Prenatal programming of sporting success: Associations of digit ratio (2D:4D), a putative marker for prenatal androgen action, with world rankings in female fencers - Bescós, R.; Esteve, M.; Porta, J.; Mateu, M.; Irurtia, A.; Voracek, M. (Journal of Sports Sciences, 2009)
Associations of the second-to-fourth digit ratio (2D:4D), a putative marker for prenatal androgen action, and of absolute finger length, a putative marker for pubertal-adolescent androgen action, with sport performance were examined in a multinational sample of 87 world-class women pe fencers. Lower (masculinized) digit ratios correlated, although not significantly so, with better current and highest past world rankings. These correlations were significant for right-hand 2D:4D with controls for the most salient factors for 2D:4D (ethnicity) and world rankings (years of international experience, height, and weight). Longer (masculinized) fingers correlated strongly with better current and highest past world rankings; these correlations became insignificant with the same controls. Replicating previous evidence for fencers, left-handedness was much more prevalent in this sample (21%) than in the female general population, and left-handers had somewhat, but not significantly so, lower 2D:4D as well as better world rankings than right-handers. These findings extend related evidence suggestive of prenatal programming of aptitude across a variety of sports, especially running and soccer. Some known extragenital effects of prenatal testosterone that contribute to the development of efficient cardiovascular systems, good visuospatial abilities, physical endurance and speed, and to the propensity for rough-and-tumble play, apparently promote sporting success in adult life.